PROFIL BERPIKIR ALJABAR SISWA SMP DALAM MENYELESAIKAN MASALAH MATEMATIKA DITINJAU DARI GAYA KOGNITIF (REFLEKTIF DAN IMPULSIF) - Pratika Maharani; Dinawati Trapsilasiwi; Erfan Yudianto; Sunardi Sunardi; Titik Sugiarti (saintifika, 2018)
The purpose of this study is to describe the profile of algebraic thinking in junior high school students in solving mathematical problems in terms of cognitive style (reflective and impulsive). The subjects used were class VIII B Arjasa 1 Junior High School as many as 25 children. Data collection in this study used two test questions, namely the MFFT test (Matching Familiar Figure Test), algebra test and interviews with four students representing different cognitive styles (reflective and impulsive) . In this study students who have reflective cognitive style and students who have impulsive cognitive style can fulfill five indicators of algebraic thinking, namely generalization, abstraction, analytical thinking, dynamic thinking, and modeling.